Supports and Barriers to Universal Design for Learning in Schools Implementing Integrated Comprehensive Systems for Equity - (:unkn) unknown (My University, 2018)
These two qualitative descriptive case studies investigated supports and barriers to integrating Universal Design for Learning (UDL) as an instructional methodology in language arts and social studies departments at an urban and a suburban high school in Wisconsin. Integrated Comprehensive Systems (ICS) implementation was determined through the Four Cornerstones – Cornerstone One: Focus on Equity, Cornerstone Two: Align Staff and Students, Cornerstone Three: Transform Teaching and Learning, and Cornerstone Four: Leverage Funding and Policy. Classroom observations were conducted of the eleven participating teachers in this study. These teachers also participated in semi-structured interviews designed to explore supports and barriers to integrating UDL as an instructional methodology. The research questions were: 1) What supports exist for integrating UDL as an instructional methodology in schools implementing ICS? 2) How do these supports bring about successful integration of UDL as an instructional methodology? 3) What barriers prevent the integration of UDL as an instructional methodology in schools implementing ICS? 4) How do these barriers prevent the integration of UDL as an instructional methodology? and 5) Why do barriers preventing the integration of UDL as an instructional methodology exist? Supports identified to integrating UDL as an instructional methodology included commitment, administrative support, freedom to experiment, funding, professional development, teacher flexibility, technology, shared expertise, co-servicing, common planning, and flexible furniture. Barriers included common curriculum and assessments, push back from central office, limited flexibility, limited commitment, limited professional development, class size and disproportionate numbers of students with high needs, no preparation time, limited class support, and limited funding. The data collected in these qualitative case studies suggests that teachers should be aligned to create Co-planning and Co-serving™ Teams (CCTs) including general education teachers, special education teachers, interventionists, Title supports, and English Language Learner (ELL) support teachers to share knowledge and expertise during a regularly scheduled co-planning time for increasing each other’s capacity to teach a broad range of students. The data also suggested that teachers benefit from regular and ongoing professional development focused on UDL to support their understanding of providing students with different ways of accessing information and demonstrating what they learn through use of their individual strengths.
Keywords: Co-planning to Co-serve; Co-teaching; Education; Inclusion; Integrated Comprehensive Systems; Universal Design for Learning